BRAC-Ain 0 Salish Kendro Joint Legal Aid Programme: a comprehensive review - Banu, Dilruba (BRAC Research and Evaluation Division (RED), 2019)
BRAC-Ain 0 Salish Kendro (ASK) joint legal aid programme was initiated to promote legal awareness among the poor along with providing them legal assistance to resolve their problems. This study intended to review BRAC-ASK joint legal aid programme at different steps of its operation. Both qualitative and quantitative data was collected for this study. Findings showed that BRAC staff could develop their capacity to implement the legal aid programme in an effective way. The programme required close supervision by BRAC and ASK at its every stage of operation, which a single PO could not ensure. The programme needed to be held more workshops and seminars at village level to make the programme widely accepted by the community people. The programme dealt with sensitive issues so liaison with the local police and the political parties was necessary for BRAC staffs personal security. The activities of panel lawyers should be strongly monitored. The paralegal sebikas can share only those activities of legal aid programme which are more convenient to them compare to other BRAC staff. BRAC members had better knowledge on different aspects of legal aid programme than that of non-members. Around one-fourth of the respondents who received assistance from BRAC evaluated the legal aid programme either fairly effective or completely ineffective to solve their problems.